2014
DOI: 10.1590/1516-635x1603257-264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus Probiotic, P22 Bacteriophage and Salmonella Typhimurium on the Heterophilic Burst Activity of Broiler Chickens

Abstract: Due to the constant evolution of industrial poultry production and the global emergence of bacterial resistance to antibiotics there has been an increasing interest in alternatives for the treatment of poultry salmonellosis, such as phage therapy and probiotics. The present study evaluated the effects of the oral administration of the bacteriophage P22 and of a probiotic, consisting of four Lactobacillus species, on the level of circulating heterophils containing a superoxide anion of oneday-old broilers chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…On the other hand, the concentration of ammonia in the excreta of poultry can be reduced by using probiotics like Enterococcus faecium and Bacillus subtilis [8], reduction of Salmonella and Campylobacter colonization [55,57,58], prevention or treatment E. coli infection in broilers [59] Regarding poultry industry in Egypt, studies have recently directed to the impact of probiotics in poultry and poultry meat production; it was found that probiotic cell-free supernatants of four probiotic strains, Lactobacillus rhamnosus, Lactobacillus fermentum, Pediococcus acidilactici and Lactobacillus delbrueckii subsp. lactis could significantly inhibit the growth of Clostridium perfringens in poultry meat during storage as well as their antioxidant effect [60].…”
Section: Monogastric Animalsmentioning
confidence: 99%
“…On the other hand, the concentration of ammonia in the excreta of poultry can be reduced by using probiotics like Enterococcus faecium and Bacillus subtilis [8], reduction of Salmonella and Campylobacter colonization [55,57,58], prevention or treatment E. coli infection in broilers [59] Regarding poultry industry in Egypt, studies have recently directed to the impact of probiotics in poultry and poultry meat production; it was found that probiotic cell-free supernatants of four probiotic strains, Lactobacillus rhamnosus, Lactobacillus fermentum, Pediococcus acidilactici and Lactobacillus delbrueckii subsp. lactis could significantly inhibit the growth of Clostridium perfringens in poultry meat during storage as well as their antioxidant effect [60].…”
Section: Monogastric Animalsmentioning
confidence: 99%
“…Studies have identified bacteriophage dietary additives that can reduce cecal Salmonella by up to 2.1 log 10 CFU/g (Kim et al, 2013) and Campylobacter by up to 2 log 10 CFU/g in the feces and 3.2 log 10 CFU/g in the cecal contents (Carvalho et al, 2010;Kittler et al, 2013), but others saw no significant effect from treatment (Kim et al, 2014), including a field trial of a commercial phage product (SalmoFREE R ) (Clavijo et al, 2019). Some trials identified orally dosed bacteriophage treatments successful in reducing Salmonella (Colom et al, 2017;Colom et al, 2015;Goncalves et al, 2014;Marietto-Goncalves et al, 2014;Nabil et al, 2018) and Campylobacter (El-Shibiny et al, 2009;Fischer et al, 2013;Hammerl et al, 2014;Richards et al, 2019), and may be followed up in the future with feed and water additive trials. A meta-analysis by Mosimann et al (2021) showed that bacteriophage treatment can reduce Salmonella and Campylobacter in poultry, and examined factors that can affect the efficacy.…”
Section: Bacteriophagementioning
confidence: 99%
“…While potentially less practical, probiotics can also be delivered to chicks orally shortly after hatch. A number of studies found that single oral doses of probiotics on day 0 or 1 of life can protect against Salmonella early in life, leading to reductions in Salmonella prevalence in the spleen and liver (Yang et al., 2014) and ceca (Higgins et al., 2010; Marietto‐Goncalves et al., 2014; Schneitz et al., 2016; Sornplang et al., 2015; Telg & Caldwell, 2009; Waewdee et al., 2012), and reducing cecal counts by 0.9–3 log 10 CFU/g (Menconi et al., 2011; Nakphaichit et al., 2019; Okamoto et al., 2018; Prado‐Rebolledo et al., 2017; Revolledo et al., 2009; Telg & Caldwell, 2009). Treatments consisting of multiple oral doses of a Lactobacillus probiotic starting from day 1 of life were also found to reduce cecal Salmonella (Chen et al., 2012; Olnood et al., 2015).…”
Section: Primary Productionmentioning
confidence: 99%
“…A number of studies found that single oral doses of probiotics on days 0 or 1 of life can protect against Salmonella early in life, where they led to reductions in Salmonella prevalence in the spleen and liver [38] and ceca [39][40][41][42][43], and reduced cecal counts by 0.9-3 log10 CFU/g [43][44][45][46][47]. Treatments consisting of multiple oral doses of a Lactobacillus probiotic starting from day 1 of life were found to reduce cecal Salmonella [48,49].…”
Section: Hatcherymentioning
confidence: 99%
“…Studies have identified bacteriophage additives which may reduce Salmonella [286] and Campylobacter [287,288], but others saw no effect from treatment [289,290]. Some trials identified orally dosed bacteriophage treatments successful at reducing Salmonella [40,[291][292][293][294] and Campylobacter [295][296][297][298], and may be followed up in the future with feed and water additive trials. A barrier to the effective use of bacteriophage treatments is the host-specificity of bacteriophage, so cocktail mixtures with a range of bacteriophage are often used.…”
Section: Bacteriophagementioning
confidence: 99%